Lymphoepithelial cyst on the tongue: case report at unusual location - Rafaella B. Leite; Mara Luana B. Severo; Patrícia T. Oliveira; Ana Miryan C. Medeiros; Carlos Augusto G. Barboza; Ericka Janine D. Silveira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Oral lymphoepithelial cyst (OLEC) is an uncommon lesion that develops in oral lymphoid tissue. The aim of the present study was to report a clinical case of OLEC in the tongue. A 22-year-old patient presented a nodular lesion, yellowish, with a softened consistency, measuring 0.5 cm in the ventral surface of the tongue. Under the clinical hypotheses of mucocele and OLEC, excisional biopsy was performed. The histopathological examination revealed a cystic lesion covered by a parakeratinized stratified squamous epithelium, which presented in its fibrous capsule a prominent lymphoid tissue. Based on the definitive diagnosis, surgical excision of the lesion was performed.